2018
DOI: 10.29252/jafm.11.03.27796
|View full text |Cite
|
Sign up to set email alerts
|

Rollover Mechanism Methodology of LNG Tank with Gas-Liquid Stratification Based on Curvelet Finite Element Method and Large Eddy Simulation Technology

Abstract: The rollover phenomenon of LNG tank has great threat to secure storage of LNG, therefore the Curvelet finite element method combing the large eddy simulation technology to analyze the rollover mechanism. Firstly, the basic principles of Curvelet transform are studied, the mathematical model and properties of Curvelet transform have been discussed. Secondly, theoretical models of rollover of LNG tank with gas-liquid stratification based on large eddy simulation are put forward, and then rollover Curvelet finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, Deshpande [61], Zhao [62], Wang [63], and Zhao [64] developed new models to predict and characterize LNG stratification and rollover behavior in storage tanks, and the models are summarized in Table 1.…”
Section: Four-stage Modelmentioning
confidence: 99%
“…In addition, Deshpande [61], Zhao [62], Wang [63], and Zhao [64] developed new models to predict and characterize LNG stratification and rollover behavior in storage tanks, and the models are summarized in Table 1.…”
Section: Four-stage Modelmentioning
confidence: 99%
“…A very important element of research on the rollover phenomenon is the numerical determination of the factors influencing the formation of cryogenic liquid stratification and modelling of heat and mass flow [38]. Many works use the finite elements method and computational fluid dynamics (CFD) method to model and predict the occurrence of the rollover phenomenon [5,[39][40][41]. Some studies investigate the effect of the forced convection caused by the cargo tank motions from sea waves on the heat and mass transfer between LNG layers and its impact on rollover occurrence [42].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that secondary backflow is caused by jets on the horizontal cross-section of the tank, and it consists of a pair of vortices. Zhao et al [35] proposed a theoretical model of gas-liquid-layered LNG tank rollover based on large eddy simulation and obtained a gas-liquid-layered LNG tank rollover curve model. Wei et al [36] carried out a numerical study on the interface instability process of multicomponent liquids.…”
Section: Introductionmentioning
confidence: 99%